Investigation on potential associations of oxidatively generated DNA/RNA damage with lung, colorectal, breast, prostate and total cancer incidence - Gao, Xin; Holleczek, Bernd; Cuk, Katarina; Zhang, Yan; Anusruti, Ankita; Xuan, Yang; Brenner, Hermann; Schöttker, Ben (Scientific reports, 2019)
Oxidative stress has been linked to cancer development in previous studies. However, the association between pre-diagnostic oxidatively generated DNA/RNA damage levels and incident cancer has rarely been investigated. Urinary oxidized guanine/guanosine (OxGua) concentrations, including 8-hydroxy-2′-deoxyguanosine, were assessed in 8,793 older adults in a population-based German cohort. 1,540 incident cancer cases, including 207 lung, 196 colorectal, 218 breast and 245 prostate cancer cases were diagnosed during over 14 years of follow-up. Associations of OxGua levels with cancer outcomes were not observed in the total population in multi-variable adjusted Cox regression models. However, in subgroup analyses, colorectal cancer incidence increased by 8%, 9% and 8% with one standard deviation increase in OxGua levels among current non-smokers, female and non-obese participants, respectively. Additionally, among non-smokers, overall and prostate cancer incidences statistically significantly increased by 5% and 13% per 1 standard deviation increase in OxGua levels, respectively. In contrast, OxGua levels were inversely associated with the risk of prostate cancer among current smokers. However, none of the subgroup analyses had p-values below a threshold for statistical significance after correction for multiple testing. Thus, results need to be validated in further studies. There might be a pattern that oxidatively generated DNA/RNA damage is a weak cancer risk factor in the absence of other strong risk factors, such as smoking, obesity and male sex.
Gesehen am 05.06.2019